ANALISIS KINERJA PUSKESMAS KARANGAYU KOTA SEMARANG - Kristiandi, Thomas Denny; D, Ida Hayu; Widowati, Nina (Journal of Public Policy and Management Review, 2015)
This study aims to analyze and describe the performance of health centers based on the dimensions of Semarang Karangayu performance and analyze the factors that support and hinder the performance of PHC Karangayu. The results showed that the performance of PHC Karangayu is good because of the five dimensions of performance, there are three dimensions that have good performance is the responsiveness, responsibility and accountability, while the other two dimensions are not well productivity and service quality dimensions and factors that support the performance of the health center is the quality of the source Karangayu human and organizational culture while the factors that hinder the performance of PHC Karangayu is the quantity of human resources, quality and quantity of infrastructure facilities and infrastructure. The conclusion of this study Karangayu PHC performance is good because of the five dimensions of performance, there are three dimensions that have good performance is the responsiveness, responsibility and accountability, while the other two dimensions are not well productivity and service quality dimensions and factors that support the performance of the health center is the quality of the source Karangayu human and organizational culture while the factors that hinder the performance of PHC Karangayu is the quantity of human resources, quality and quantity of infrastructure facilities and infrastructure. Based on this conclusion, the researchers recommend to the health center to submit proposals Karangayu procurement admission selection medical and non medical personnel and increase the number of facilities and infrastructure. PHC Karangayu can also use outsourcing to add non-medical personnel.Â Â